Final Pre-40S Maturation Depends on the Functional Integrity of the 60S Subunit Ribosomal Protein L3 - García-Gómez, Juan J.; Fernández-Pevida, Antonio; Lebaron, Simon; Rosado, Iván V.; Tollervey, David; Kressler, Dieter; de la Cruz, Jesús (PLoS genetics, 2014)
Ribosomal protein L3 is an evolutionarily conserved protein that participates in the assembly of early pre-60S particles. We report that the rpl3[W255C] allele, which affects the affinity and function of translation elongation factors, impairs cytoplasmic maturation of 20S pre-rRNA. This was not seen for other mutations in or depletion of L3 or other 60S ribosomal proteins. Surprisingly, pre-40S particles containing 20S pre-rRNA form translation-competent 80S ribosomes, and translation inhibition partially suppresses 20S pre-rRNA accumulation. The GTP-dependent translation initiation factor Fun12 (yeast eIF5B) shows similar in vivo binding to ribosomal particles from wild-type and rpl3[W255C] cells. However, the GTPase activity of eIF5B failed to stimulate processing of 20S pre-rRNA when assayed with ribosomal particles purified from rpl3[W255C] cells. We conclude that L3 plays an important role in the function of eIF5B in stimulating 3' end processing of 18S rRNA in the context of 80S ribosomes that have not yet engaged in translation. These findings indicate that the correct conformation of the GTPase activation region is assessed in a quality control step during maturation of cytoplasmic pre-ribosomal particles.